URGENSI PEMERINTAH DAERAH TERKAIT PELAKSANAAN ASAS PEMERINTAHAN YANG BAIK DALAM LINGKUP PEMBINAAN DAN PENGAWASAN - Agustina; Dhea Preyanita Oktari; Hizkia Herlina Avangelista Silalahi; Rafizah Purnama (BULLET : Jurnal Multidisiplin Ilmu, 2022)
The Regional Government is the regional head as an element in the implementation of Regional Government in charge of leading the implementation of the government element into an autonomous regional authority. In order for the implementation of government affairs to be carried out, it must be based on the principles of good governance. Good governance is the implementation of management that is responsible and runs with efficient democratic principles. Basically, this is a concept that refers to the process of achieving decisions and being carried out together and can be accounted for. One of the roles of the regional government is in the scope of guidance and supervision of the implementation of regional government in accordance with the mandate of the Republic of Indonesia Government Regulation Number 20 of 2001.